STRATEGI PENINGKATAN KETAHANAN EKONOMI UNTUK PERIKANAN BERKELANJUTAN BERBASIS KONSEP BLUE ECONOMY - Diana Puspitasari; Amalia Nur Chasanah; Masitha Fahmi Wardhani (Value : Jurnal Manajemen dan Akuntansi, 2023)
The difficulties and fisheries industry in Indonesia continues to grow in accordance with the 2013–2025 Marine and Fisheries Sector Medium Term Development Plan which refers to the concept of the Blue Economy. The purpose of this research is to find out the implementation of business models and strategies for sustainable sustainability that adopt the Blue Economy concept. This research is a qualitative research using a narrative approach to obtain data related to sustainable strategies in accordance with the Blue Economy concept that can be developed on research objects. The results of the study explain that the success of blue economy-based industries must be supported by a strong commitment between various parties in real action as a form of overall development support, so the direction of program policies must be innovative and creative through a touch of technology. Utilization of digital technology can help fishery businesses based on the concept of a sustainable blue economy, processing all fishery resources owned to be utilized for the welfare of the community without destroying the existing ecosystem. Digital transformation can be a bridge for business owners with markets as consumers, they interact efficiently with each other in meeting the production chain of market needs. Innovation in digital transformation must continue to be carried out and supported by the skills of its human resources to increase attractiveness and expand market access. Keywords: Blue Economy, sustainability, digital transformation.